The unexcused error in algerian social security legislation between legislation and application - Labbani, Wafa (Journal of Human Sciences, 2023)
This study aims to identify the unexplained error provisions of Algeria’s Social Security Disputes Act And this is through the search for what it is and the problems arising from its application, This mistake is made by the employee or his follower which leads to the worker’s injury to a work accident or occupational illness Social Security Authority ", entitles both the Social Security Authority and/or the Social Security Insured, when proven, to recourse against the perpetrators. We concluded that this error raises several legal and applied problems. of which it is difficult to prove to the social insured, in our view, because the latter benefits from compensation for occupational risks partially and automatically without the need to prove the employer’s fault.